Use Consumable Salt Concentration in Process Flotation Intestine Worm Eggs - Rony Puasa; Febrianti Jakaria (Jurnal Media Analis Kesehatan, 2023)
Salt is a chemical that is often used in families as a food flavoring or as a food preservative with the main substance being Sodium Chloride (NaCl). Re-fined salt as an ingredient for public consumption can be used in the laboratory as an alternative material to replace saturated NaCl (pa) for flotation of nematode worm eggs. The purpose of this study is to find out certain brands of consumable salt that can be used to float in-testinal nematode worm eggs. Method this research is a laboratory experiment where samples of consumed salt are treated and suspension is added and then the results of the treatment are observed microscopically. The results of this research is a good concentra-tion for the flotation process of 4 brands of consumable salt is 32% and the brand that can be used as a medium in the flotation process is the BTM salt brand. Conclusion this research is the BTM consumption salt brand provides good results in the flotation process by floating three species of intestinal nematose eggs, namely; round-worms, whipworms, hookworms (N. americanus and A. duodenale)